The Influence of Booklet “Happy Entrepreneurship” toward the Entrepreneurship Motivation - Marlynda Happy Nurmalita Sari; Bekti Putri Harwijayanti (Poltekkes Kemenkes Palu, 2022)
Intoduction: Students need to be motivated from an early age about entrepreneurship to be better prepared to become graduates who will create employment opportunities. Purpose: to know the effect of the booklet